2022
DOI: 10.1155/2022/1557256
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Efficacy of LSC and TVT-O for Stress Urinary Incontinence Complicated with Pelvic Organ Prolapse and Factors Influencing Postoperative Urinary Function Recovery

Abstract: Pelvic organ prolapse is caused by various causes, which leads to the weakness of the tissue supporting the pelvic floor and then causes the downward displacement of female reproductive organs and adjacent organs. Clinical studies have shown that pop is often associated with stress urinary incontinence. This research project aimed to clarify the clinical effect of laparoscopic sacrocolpopexy (LSC) and tension-free vaginal tape obturator (TVT-O) for stress urinary incontinence (SUI) complicated with pelvic orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%